Chemical composition, antioxidant and antimicrobial activities of Vaccinium macrocarpon (Ericaceae) and Camellia sinensis (Theaceae) extracts - O. Maslov; M. Komisarenko; S. Ponomarenko; S. Kolisnyk; T. Osolodchenko; M. Golik (Regulatory Mechanisms in Biosystems, 2024)
In the modern scientific community, considerable attention is given to studying the pharmacological activity of catechin and anthocyanin derivatives. However, a comparative analysis of the antioxidant and antimicrobial activities of extracts rich in anthocyanins and catechins has not been previously conducted. So, the purpose of this work was to study and compare phytochemical composition, antimicrobial and antioxidant potential of Vaccinium macrocarpon L., Ericaceae fruit thick and Camellia sinensis L., Theaceae leaf liquid extracts. The quantification of biologically active substances (BAS) was accomplished with spectrophotometric, titrimetric and HPLC methods of analysis; antioxidant activity was determined by the potentiometric method; antimicrobial and anti-fungi effects was evaluated by the well method and minimum inhibition concentration. The total content of phenolic compounds was 0.47% and 10.10%, organic acids – 4.27% and 1.60% for V. macrocarpon fruit thick and C. sinensis leaf extract. The total content of catechins in the C. sinensis leaf extract was 105,000 mg/kg, where epicatechin-3-O-gallate dominated (37300 mg/kg). The total content of anthocyanins in the V. macrocarpon fruit thick extract was 1280 mg/kg, where peonidin-3-O-galactoside dominated (408 mg/kg). Both extracts possessed a high antioxidant potential, and effective antimicrobial and anti-fungi effects. The antioxidant, antimicrobial and anti-fungi activity of V. macrocarpon fruit extract was higher than C. sinensis leaf extract. In addition, we assumed that anthocyanins had higher antioxidant, antimicrobial and anti-fungi properties than catechins. These findings would promote application of V. macrocarpon fruits extract as pharmaceuticals and nutraceuticals.